Synthesis of Azahelicene N‐Oxide by Palladium‐Catalyzed Direct CH Annulation of a Pendant (Z)‐Bromovinyl Side Chain. Issue 36 (19th July 2013) - Kaneko, Eri; Matsumoto, Yuki; Kamikawa, Ken
<x xml:space="preserve">Abstract</x> Driving benzene round the twist: Azahelicene derivatives were synthesized in high yields by utilizing palladium‐catalyzed CH annulation reactions (see scheme). Functionalization at the C5 position in 6‐azahelicene by using palladium‐catalyzed CH arylation also gave coupling products in good yields. A tandem intra‐ and intermolecular double CH coupling reaction was performed to give a functionalized helicene in a one‐pot procedure.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>